Neolithic site Pod Jarugom (In situ, 2024)
In March 2022, archaeological trial trenching was carried out at the Pod jarugom site in Podgrađe. The excavation was conducted with the aim of determining the stratigraphic and cultural relationships at the site, which was discovered in 1976 at the foot of Perušićka kosa by Š. Batović. A cultural deposit dating to the Middle Neolithic, that is the Danilo culture, was found in the excavated area.
Keywords: Podgrađe; trial excavations; Neolithic; Danilo culture